Minimizing Dynamic Loading Resonance of Battery Pack Subjected to Road Profile Loads. Issue 1 (March 2021) - Abdillah, Muhammad Farkhan; Budiman, Bentang Arief; Prasetio, Ignatius Pulung; Sambegoro, Poetro Lebdo
Abstract: One of the main problems in designing battery packing for electric vehicles is the appearance of deformation in the components due to vibration generated by road profile. The vibration brings the most significant effect on the battery packing due to low frequency and high amplitude. Resonance occurs at low frequency since most of the E-trike components have a low natural frequency. This should be avoided to increase the reliability of the battery pack due to mechanical loadings. Modal analysis, Quarter Car Model (QCM), and optimization were conducted in this work. Modal analysis is used to find the natural frequencies of the battery pack on several modes of vibrations. Simulink of the Quarter Car Model (QCM) produces the load from the road profiles based on ISO 8608. The load from the road profiles is used as the input in the Ansys 16.0 Harmonic Analysis. The output is the deformation frequency response for the bottom side case of the battery pack. To reduce the outcome of resonance, a damping mechanism is selected to reduce maximum amplitude from road profile at a resonance frequency. The simulation results show that the damping mechanism is the suitable technology to decrease the major amplitude of the deformations from road profile with reduction up to 54% lower than the previous model. The lower deformations of the battery pack component reduce the battery pack's possible accident due to vibration.